Value Engineering Implementation in an Integrated Arts Laboratory Project - Triswandana, I Wayan Gde Erick; Agus Arya Pramana Maharat , Fortunata (Bulletin of Civil Engineering, 2026)
Infrastructure development projects often face design changes that affect specifications, volumes, and resource allocation, thereby requiring adjustments to cost estimates. Conventional cost-cutting practices frequently compromise quality, underscoring the need for systematic approaches such as Value Engineering (VE). This study applies VE in conjunction with the Pareto Distribution Principle to optimize cost efficiency and functional performance in the construction of an integrated arts laboratory building. A descriptive quantitative method was employed, encompassing the phases of information gathering, functional analysis using the Function Analysis System Technique (FAST), creative brainstorming, evaluation, and presentation. Pareto analysis revealed that 78.99% of project costs were concentrated in architectural, structural, and roofing works, which became the focus of VE. Functional analysis identified opportunities to substitute lower-order functions, particularly in formwork, door and window installations, and ceiling work. Comparative evaluation of alternative designs demonstrated significant improvements: composite slabs enhanced installation efficiency despite slightly higher initial costs; aluminium frames for doors and windows reduced life cycle costs by 30.8 million IDR while improving durability; and PVC ceilings achieved savings of 148.9 million IDR with superior performance indicators. Overall, VE implementation yielded cost savings, reduced material waste, and improved technological innovation without compromising quality. The integration of VE and Pareto analysis thus provides a comprehensive framework for achieving optimal value in construction projects, balancing cost efficiency, functionality, and sustainability.